THE ENERGY UNION AND VISEGRAD FOUR COOPERATION - Yakovenko, K. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The following article argues that energy security is an extremely important challenge for the countries of the European Union. Economically and democratically weakly-developed countries hold a constant fight, both open and hidden, for preserving and enforcing their energy influence in the world. Russia is the most vivid of such examples. Considering the events in the East of Ukraine, its closest European neighbours – countries of the Visegrad Four Group - should unite their efforts together and re-think their energy policies in terms of security and diversification. Establishing the EU Energy Union might be a solution.